Provision of Iron and Folic Acid Supplementations for Pregnant Women in Public and Private Sectors of Tabriz, Iran - Hossein Jabbari; Fariba Bakhshian; Hossein Alikhah; Reza Piri; Mohammad Naghavi-Behzad; Farid Karkon Shayan (Iranian Journal of Neonatology, 2015)
Background: This study aimed to investigate different methods used to provide necessary supplementations for pregnant women and obtain reliable data about the general status of health promotion during pregnancy. Methods: This descriptive, cross-sectional study was conducted on 401 pregnant women referring to different women’s hospitals of Tabriz, including Alzahra, Taleghani, 29-Bahman, Zakariya, Shafa, and Shams from March 2011 to September 2013. Subjects were selected using simple random sampling and had prior experience of childbirth. Results: In this study, prenatal care was provided for all the pregnant women at public (55.8%) and private sectors (44.2%). Iron supplementation used by the subjects included ferrous sulfate (150 mg) + folic acid (0.5 mg) (20.2%), regular-release ferrous sulfate (325 mg) (70.4%), folic acid (0.1 mg) + ferrous sulfate (200 mg) (6.5%), and vitamin B12 (15 mg) + ferrous fumarate (350 mg)+ vitamin C (150 mg) + folic acid (1 mg) (1.6%). Supplementations were provided before (56.7%) or after (43.3%) the onset of pregnancy. In total, 40.9% of the subjects received family planning care, 44.7% of whom referred to medical centers, 34.6% referred to health houses, 12.3% consulted gynecologists, 2.8% consulted midwives and 5% received traditional care. Conclusion: According to the results of this study, general status of iron and folic acid supplementation, their provision and average use of these substances were suboptimal. However, status, provision and use of iron were significantly more efficient than folic acid.